The Design and Analysis of a Child Seat for a Motorcycle - Ariq Naufal Rabbani; Ken Risa Ayu Ndaru Ningrum; Alvin Widjaya; Farid Triawan (President University, 2020)
This paper discusses the methodology of design and analysis of a child seat for motorcycles. After realizing the dangers of an unrestrained child in motorcycles, this seat offers a solution to the problem. The seat features sliding beams that allow the user to access the under-seat compartment of the motorcycle and the fuel tank, without requiring any disassembly of the child seat. The dimensions are measured and considered when designing in a graphical application. Once the assembly drawing is completed, the seat is analyzed to identify critical parts of the seat to ensure failure does not occur. It is concluded that our design can withstand static loading but is predicted to fail due to fatigue after 81× 103 cycles under the assumption of accelerating from 0 to 50 km/h in 5 seconds. However, since that is not deemed to be fully optimized due to having a finite life, the material and dimensions are changed so that an infinite life can be predicted.